Obsolete vocabulary and features of its diﬀerentiation in dictionaries of the modern Belarusian literary language - Makarevich, Aliaksandr V. (Journal of the Belarusian State University. Philology, 2023)
The article outlines the status of obsolete vocabulary in the system of the modern Belarusian literary language. The representation of obsolete nominations, including stylistically colored units, in the dictionaries of the modern Belarusian language is analysed. The marking system for denoting obsolete vocabulary in directories is investigated. The inconsistency of using these markers by authors of dictionaries should be singled out. The terms уст., заст. and саст., used to fx obsolete units in the dictionaries of the modern Belarusian literary language, are specifed.
Keywords: lexicography; obsolete nominations; stylistic mark; functional-stylistic marks; archaism; historicism; sphere of the word usage